Factors Associated with Intubation Time and ICU Stay After CABG - Suzanny Flegler; Flavia Marini Paro (Brazilian Journal of Cardiovascular Surgery, 2015)
ABSTRACT OBJECTIVE: The aim of this study was to identify factors associated with intubation time and intensive care unit stay after coronary artery bypass grafting with cardiopulmonary bypass. METHODS: This was a retrospective study, whose data collection was performed in the hospital charts of 160 patients over 18 years, who underwent surgery from September 2009 to July of 2013 in a hospital in the state of Espirito Santo, Brazil. RESULTS: The mean age of the subjects was 61.44±8.93 years old and 68.8% were male. Subjects had a mean of 5.17±8.42 days of intensive care unit stay and mean intubation time of 10.99±8.41 hours. We observed statistically significant positive correlation between the following variables: patients' age and intubation time; patients' age and intensive care unit stay; intubation time and intensive care unit stay. CONCLUSION: In conclusion, the study showed that older patients had longer intubation time and increased intensive care unit stay. Furthermore, patients with longer intubation time had increased intensive care unit stay.